PROSPECTS AND PRACTICES FOR THE DEVELOPMENT OF MEDIA LITERACY IN UZBEKISTAN (Academia Science Repository, 2023)
This scientific article examines the prospects and practices for the development of media literacy in Uzbekistan. With the rapid advancements in digital technology and the widespread availability of media content, media literacy has become a crucial skill for individuals to navigate the information landscape effectively. This article explores the current state of media literacy in Uzbekistan, identifies the challenges faced, and highlights potential strategies and practices to enhance media literacy education in the country. By addressing these issues, Uzbekistan can foster a population that is critical, informed, and responsible in their media consumption and production.